PID tuning control strategy using Cuckoo search algorithm for pressure plant - Singh, K.S.M.J. (Institute of Electrical and Electronics Engineers Inc., 2017)
Plant process is a form of a process which requires a robust controller to regulate the process. Therefore, tuning of the controller for the specific process is necessary and each controller is process specific. This paper focuses on using the biomimetic algorithm due to its' competency to improve the system performance in terms of rise time, settling time and overshoot to regulate a closed loop pressure system. These biomimetic algorithms excel in optimization problems. Algorithms that will be investigated are the Ziegler-Nichols (ZN) and Cuckoo Search (CS) in tuning the Proportional-Integral-Derivative (PID) controller for a closed loop pressure plant system. © 2016 IEEE.